Assessment of Operative Management of Bimalleolar Fractures of Ankle Joint - Kumar, Pravas; Abhishek, Dr; Singh, Shree Prakash (Asian Journal of Medical Research, 2019)
Background: Bimalleolar fractures have shown to have worse outcomes. The present study was conducted to assess operative management of bimalleolar fractures of ankle joint. Subjects and Methods: The present study was conducted on 60 cases of bimalleolar fractures of ankle joint. Patients with compound fractures, pilon fractures, syndesmotic injuries were excluded. In all patients, reason of fracture and operative outcome was recorded. Results: Functional outcome was excellent seen in 15, good in 30, fair in 12 and poor in 3. The difference was significant (P< 0.05). Post operative complications were superficial skin infection seen in 2 and restricted ankle movement in 1. Conclusion: Bimalleolar fractures of ankle joint are common amongst males. In maximum cases, good results were obtained.